Genotypic and Phenotypic Study of PDCD4 gene Concerning micro RNA-21 and micro RNA-449b Polymorphism in Breast Cancer - Al-Janaby, Mohammed Salih; Al-Ani, Mohammed Q.; Lafta, Fadhel M. (Iraqi Journal of Science, 2025)
Breast cancer is a heterogeneous disease with a significant impact of genes involved in apoptosis. Hence, this study aims to assess the contribution of programmed cell death protein 4(PDCD4) miR-21, miR-449b and PDCD4 genes polymorphism in breast cancer pathogenicity. A total of 180 blood samples were collected from Iraqi women aged between 15-80 years, 120 samples were included from breast cancer patients (divided into two groups of 60 patients under treatment and 60 post treatments and recovery) then 60 healthy women as a control group. The extracted genomic DNA was amplified by PCR technique for the loci of interest and PCR products of the tested samples were genotyped using TaqMan real time fluorescent oligonucleotide for SNPs analysis. PDCD4 protein concentration in serum was estimated utilizing ELISA. The results showed significant association (P = 0.016) of miR-449b rs10061133:A>G polymorphism (AA, AG and GG) on the PDCD4 serum levels (3.62 ng/L, 4.75 ng/L and 2.58 ng/L respectively). PDCD4 serum showed to differ significantly (p = 0.001) among the investigated groups: treatment (5.39 ng/L), post-treatment (3.42ng/L), and control (3.19 ng/L). An evaluation of the effects of breast cancer risk factors on the studied parameter revealed that breastfeeding appears to significantly influence PDCD4 serum levels. Women who breastfed exhibited a mean PDCD4 concentration of 4.40 ng/L, compared to 3.25 ng/L for those who did not breastfeed (P=0.026). Additionally, the AUC value (0.7) suggests that PDCD4 protein could be a good predictive marker for treatment response. Overall, the phenotypic expression of PDCD4 demonstrated to be significantly influenced by polymorphisim of PDCD4, miR-21 and miR-449b SNPs, with a considerable impact of breastfeeding in increasing PDCD4 levels that could be utilized to promote breast cancer prevention strategies.